2007
DOI: 10.1063/1.2798806
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium shapes and stability of a liquid film subjected to a nonuniform electric field

Abstract: Stresses induced by a spatially nonuniform electric field acting on an initially flat fluid-fluid interface can (i) be exploited beneficially to pattern polymer microstructures without the use of resists, exposure, development, and etching, but (ii) cause undesirable nonuniformity in film thickness in precision coating processes. The equilibrium shape of an interface separating a liquid film from an ambient fluid subjected to a uniform electric field is flat so long as the field strength is below a critical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Noting that c 3 (t) comes from the Maxwell stresses, we infer that the electrical stresses only induce a transient flow, which vanishes at steady state, inducing a permanent deformation in the process. In fact, previously Yeoh et al (2007) have shown that the Maxwell stresses can lead to a deformed equilibrium shape of a liquid-gas interface, in the presence of a modulated potential. We thus conclude that at O(Ca 2 ) of deformation (note that O(Ca) velocities lead to the O(Ca 2 ) deformation), both the components of the surface potential as well as the Maxwell stresses contribute, as claimed in the previous section.…”
Section: The O(ca) Solutionsmentioning
confidence: 97%
See 3 more Smart Citations
“…Noting that c 3 (t) comes from the Maxwell stresses, we infer that the electrical stresses only induce a transient flow, which vanishes at steady state, inducing a permanent deformation in the process. In fact, previously Yeoh et al (2007) have shown that the Maxwell stresses can lead to a deformed equilibrium shape of a liquid-gas interface, in the presence of a modulated potential. We thus conclude that at O(Ca 2 ) of deformation (note that O(Ca) velocities lead to the O(Ca 2 ) deformation), both the components of the surface potential as well as the Maxwell stresses contribute, as claimed in the previous section.…”
Section: The O(ca) Solutionsmentioning
confidence: 97%
“…Focusing particularly on the electrohydrodynamics of superimposed fluids in the presence of a modulated surface potential, such systems have been shown (Schäffer et al 2000(Schäffer et al , 2001Verma et al 2005;Yeoh, Xu & Basaran 2007;Esmaeeli & Reddy 2011) to cause interesting pattern formation. The pioneering work of Schäffer et al (2000) demonstrated that application of a non-uniform electric field can lead to the formation of pillar-like patterns replicating the shapes of the electrodes in thin polymeric films.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A good deal of analytical efforts have been done to explore the mechanism for such amazing phenomena [4][5][6][7][8][9][10][11] . The linear stability analysis showed that the thickness ratio ξ of the air gap to the film layer is critical in determining the interfacial patterns [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%